Whistleblowing Determinants: The Interaction Between Micro Social Ethical Environment And Organizational Ethical Leadership - Alfa Laili; Tito IM. Rahman Hakim; Prasetyono Prasetyono (Jurnal Reviu Akuntansi dan Keuangan, 2022)
This paper examines the influence of organizational commitment and microsocial ethical environment on internal whistleblowing intentions. This paper also investigates the moderating effect of organizational ethical leadership on organizational commitment and microsocial ethical environment. A total of 197 students at universities in Madura became respondents to this study. The sample is filtered from students in Madura Universities who join student organizations with snowball sampling. The hypotheses are tested using the partial least square (PLS) technique. The findings indicate that support from an ethical environment is associated with students' whistleblowing intentions, while organizational commitment is not significantly associated with whistleblowing intentions. Organizational ethical leadership is revealed to strengthen the effect of organizational commitment and to weaken the impact of microsocial ethical environment on internal whistleblowing intentions. The findings of this study lead researchers to conclude that "safety" is the driving factor to report fraud, not "responsibility" or "bravery". The rectorate in higher education institutions in Madura also prompted the implementation of an official whistleblowing system and ethics training so students who join student organizations feel safe and keep sensible of wrongdoing around them.